2014
DOI: 10.1111/pde.12344
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Screening in Infants with Infantile Hemangiomas before Propranolol Treatment

Abstract: There is no uniform pretreatment cardiac evaluation for infants treated with oral propranolol, which is now the drug of choice for hemangiomas of infancy requiring systemic medical intervention. The aim of this study was to report and evaluate the findings of pretreatment cardiac evaluation. Data were reviewed for patients evaluated by a single hemangioma specialist and a single pediatric cardiologist prior to initiation of propranolol for infantile hemangioma. Cardiac evaluation included a complete echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 28 publications
1
25
2
4
Order By: Relevance
“…In these cases, consultation with a paediatric cardiologist is mandatory. Since all other possible cardiac contraindications can be detected by history, physical examination, a routine echocardiography, is not essential unless there is a specific clinical indication [7,18]. Obviously, baseline values are required for heart rate and blood pressure.…”
Section: Pretreatment Evaluation and Contraindicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these cases, consultation with a paediatric cardiologist is mandatory. Since all other possible cardiac contraindications can be detected by history, physical examination, a routine echocardiography, is not essential unless there is a specific clinical indication [7,18]. Obviously, baseline values are required for heart rate and blood pressure.…”
Section: Pretreatment Evaluation and Contraindicationsmentioning
confidence: 99%
“…The standard dose in the majority of studies reported to date is 2 mg/kg/day [3,4,7,26,28,32,44,50,54,56] with a range of dosing between 0.5 and 3.0 mg/kg. As demonstrated in the multicenter study [40], 3 mg/kg/day is superior to 1 mg/kg/day, but studies comparing 2 and 3 mg/kg/day have not been reported yet.…”
Section: Initiation Of Therapy and Dosagementioning
confidence: 99%
See 1 more Smart Citation
“…However, pretreatment cardiac screening appears to be of limited value in patients with an unremarkable cardiac history and examination. [176][177][178][179] Relative contraindications to the use of propranolol for IH include cardiogenic shock, sinus bradycardia, hypotension, heart block greater than the first degree, heart failure, bronchial asthma, and known hypersensitivity to the drug (Table 5). 161 Special precautions have been suggested for children diagnosed with PHACE syndrome and significant intracranial vascular anomalies because of the theoretically increased risk of acute ischemic stroke.…”
Section: Management Of Ulcerated Ihsmentioning
confidence: 99%
“…The use of b-blockers can be also be associated with adverse cardiac effects, including bradycardia and hypotension, both of which are generally asymptomatic and do not require intervention. 177 Less common complications include bronchospasm and hypoglycemia, the latter of which has the potential to induce seizures. 159,161,180,181 In a systematic review of propranolol treatment of IH, there were 371 total adverse effects reported in 1189 patients.…”
Section: Management Of Ulcerated Ihsmentioning
confidence: 99%